Pengabdian Masyarakat oleh Mahasiswa (PMM) UMM Melalui Pendampingan Belajar pada Anak-anak TK Dharma Wanita Persatuan 1 Sengkaling - Fajar Wati, Indah; Fitriyah, Elvin; Asfara Mahila, Hilya; Muniroh, Riq’atul (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Community Service Activities by Students (PMM) of the University of Muhammadiyah Malang is a form of contribution in helping solve problems that exist in community life. The mechanism for this service is carried out by making proposals, submitting permits for service locations, preparing service, implementing service, evaluating and making reports. Learning assistance carried out by Students (PMM) Group 97 Wave 3 using a direct learning assistance model at Dharma Wanita PBB 1 Sengkaling Kindergarten. This service aims to help teachers at Dharma Wanita PBB 1 Sengkaling Kindergarten in the learning assistance process. The activities carried out by the 97 PMM UMM Group in learning assistance were learning calistung (reading, writing, calculating), making crafts, and holding coloring competitions. These activities were supported and given positive responses by the teachers at Dharma Wanita PBB 1 Sengkaling Kindergarten.The service activity ended with making window decorations for display in the children's class because the color of the old decorations had faded so they had to be replaced with new decorations. With the new decorations, it is hoped that the children of Dharma Wanita PBB 1 Sengkaling Kindergarten will be more cheerful and enthusiastic in learning.